A water-soluble antimicrobial acrylamide copolymer containing sulfitobetaine for enhanced oil recovery1. Issue 64 (12th July 2015) - Gou, Shaohua; He, Yang; Ma, Yongtao; Luo, Shan; Zhang, Qin; Jing, Dong; Guo, Qipeng
<x xml:space="preserve">Abstract</x> A novel antimicrobial copolymer containing sulfitobetaine is studied and has excellent application potential in EOR.